Triphenylphosphine‐containing microcapsules fabricated from Pickering emulsions as a thermal latent curing accelerator for an epoxy/anhydride system. Issue 12 (18th June 2021) - Gou, Haolan; Zhang, Bowen; Wei, Wei; Fei, Xiaoma; Li, Xiaojie; Liu, Xiaoya
Abstract: Latent curing accelerators are essential for application to one‐component epoxy systems in various industries, such as coatings, adhesives and electronic packaging. Herein, we developed organic–inorganic hybrid microcapsules encapsulating triphenylphosphine (TPP) by Pickering emulsion polymerization of styrene and methoxyethyl methacrylate with dimethoxydiphenylsilane‐modified silica nanoparticles as emulsifiers. The microcapsules were further surface‐modified by epoxy silane and employed as a thermal latent curing accelerator for an epoxy/anhydride system. Good dispersibility and interfacial bonding of the hybrid microcapsules with the resin matrix were observed. Compared with TPP, the microcapsule‐type accelerator endowed the one‐component epoxy curing system with significantly enhanced storage stability at room temperature of 25 °C (a pot life of 20 days) and a comparable curing activity at high temperature. The activity of the encapsulated accelerator can be blocked and released rapidly and effectively with increasing temperature to trigger the segmental motion of the polymeric microcapsules. Furthermore, the addition of microcapsules increased the glass transition temperature and thermal stability of the epoxy thermosets owing to the organic–inorganic hybrid character. Moreover, the toughness of the cured resin was also improved. Therefore, the latent curing accelerator demonstrated a promising prospect for application in high‐performance one‐pot epoxy formulations. © 2021 Society of Industrial Chemistry. Abstract : Triphenylphosphine‐containing microcapsules were successfully synthesized and then employed as a thermal latent curing accelerator for an epoxy/anhydride system, showing good dispersibility and excellent storage stability.